Optimization of bleaching earth and extraction of free fatty acid (FFA) in palm oil refinery process - Siti Haizan, Mohd Mukhtar Affandi (2015)
Physical refining has become the major processing route for crude palm oil in Malaysia. Degumming, bleaching and deodorization are essential processes that involves in palm oil refining. The purpose is the removal of gums, trace metals, pigments, peroxides, oxidation products and other breakdown products in the crude oil by adsorption on the active surface of the bleaching earth to improve colour and stability of the final oil (Siew et al., 1992). This research aims to study the Optimization of Bleaching Earth and Extraction of Free Fatty Acid (FFA) in Palm Oil Refinery Process which involves process of degumming and bleaching using neutral and acid-activated clays. Degumming is the pre-treatment stage of physical refining crude palm oil and these stages are identified as the major contributors to the total operating cost of the plant due to the cost of chemicals (phosphoric acid and bleaching earth) that are being used in these processes .Bleaching absorbs the undesirable impurities and other pigments. It also reduces the oxidation products, absorbs the phospholipids precipitated by phosphorus acid, and removes any excess present in the oil. Last stage for physical refining is deodorization. The pre-treated oil is deoerated and then heated to deodorization temperature and pressure. Under these condition , which the free fatty acids, which are still present in the oil are distilled together with the more volatile odoriferous and oxidation products such as aldehydes and ketone, which otherwise will affect the odor and the taste of the oil. In this research, a process model for degumming and bleaching operation will be designed in order to help the refiner‘s to predict the exact ratio of phosphoric acid and bleaching earth to the crude palm oil. By doing so, we could reduce the operating costs and time of the overall palm oil refining process.